Pengembangan Aplikasi Mobile Plant-tagging ‘Pelurutaloka’ sebagai Media Pembelajaran Biologi Keanekaragaman Hayati - Hidayat, Muhammad Luthfi; Mahatama, Duta Saksena; Suryani, Titik; Sari, Siti Kartika (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aims to develop a web-based mobile plant-tagging application that connects local plant species to scientific information through QR codes, which emphasizes contextual, technology-assisted learning grounded in local potential. The resulting educational media, titled Pelurutaloka (an acronym for Pembelajaran Luar Ruang Tanaman Lokal, or Outdoor Learning of Local Plants), is specifically designed to be pedagogically relevant and to serve as a foundation for future studies in local natural resources.This study adopts a Research and Development (R&D) methodology using the 4D model (Define, Design, Develop, Disseminate), with development limited to the evaluation/revision stage. The evaluation phase employed a 14-item Likert-scale questionnaire, which demonstrated high levels of validity and reliability based on expert review and Rasch model analysis (reliability = 0.72). Further Rasch analysis revealed a unidimensionality value of 40.2%, exceeding the acceptable threshold of 20%, indicating that the instrument effectively measured a single construct. The primary contribution of this research lies in the creation of a web-based, mobile-accessible biology learning media designed for outdoor contexts, offering an engaging, technology-enhanced learning experience that promotes student activity and interaction with the environment. This study recommends broader dissemination of the Pelurutaloka platform and its implementation in outdoor biology education, particularly through collaborative, active learning models such as problem-based learning (PBL) and project-based learning (PjBL).